RE-DEVELOPMENT OF TOURISM AREA IN SUMBER JENON SPRING WATER TAJINAN SUB DISTRICT, MALANG REGENCY - Reza, Mohammad; Witjaksono, Agung (Journal of Sustainable Technology and Applied Science (JSTAS), 2020)
The area of Jenon Spring Water has been determined as tourism development area in Malang Regency. Public facilities and services are a variety of physical buildings and structured programs that play a role in improving the comfort of a residential environment. Public and social services and facilities are very important in the life of city residents. This research is aimed to arrange the spatial development brief of Jenon Spring Water. The method used in this research is descriptive qualitative method. The research result show that regional arrangement is needed. Where in the area arrangement in Sumber Jenon carried out in this project has a positive effect in Gunungronggo Village, which can improve the economy of the Gunungronggo Village community and improve the quality of Human Resources in Gunungronggo Village by adding a souvenir store and other facilities in Sumber Jenon.